Teks Pawarta dalam Buku Pendamping Materi Pengayaan Asah Basa Jawa untuk SMP/MTs Kelas VIII sebagai Analisis Kajian Teks Eksposisi - Reny Anindhita Safarina; Bambang Sulanjari (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2022)
Exposition text is a text that contains information in it with the aim of providing information or knowledge for the reader. Exposition text is non-fiction so that the text must contain things such as factual and verifiable statements as well as real events. useful for readers. In learning activities, for example language subjects, students are introduced to various types of texts with the aim that students are able to distinguish and understand each type of text. As written in this study, in learning Javanese, students are presented with a Javanese news exposition text that contains information about an event in an area. The news text provides detailed information about the occurrence of these events based on the results of interviews conducted by the news writers. In order to be called an exposition text, every text that is included as an expository text must have a certain structure so that the information conveyed is really short, concise, clear and can be understood by the reader. The news text must include 5W+1H questions so that the news can be considered complete and clear. The news text which is the object of this research will be analyzed its structure according to the structure of the exposition text and described through a qualitative descriptive method that describes the analysis of the structure of the text as a whole. The news text is analyzed for the completeness of the structure of the text whether it is in accordance with the structure of the exposition text by understanding the content of the news text that is presented. This research was made as a final project for the Text Study course which aims to make students understand what has been taught during the lecture so that they can apply it in this research.